Early detection of lysosomal diseases by screening of cases of idiopathic splenomegaly and/or thrombocytopenia with a next‐generation sequencing gene panel - Gloria Muñoz; David García‐Seisdedos; Crina Ciubotariu; Miguel Piris‐Villaespesa; Marta Gandía; Fernando Martín‐Moro; Luis G. Gutiérrez‐Solana; Marta Morado; Javier López‐Jiménez; Antonio Sánchez‐Herranz; Jesús Villarrubia; Francisco J. delCastillo (JIMD Reports, 2020)
Abstract Lysosomal diseases (LD) are a group of about 70 rare hereditary disorders (combined incidence 1:5000) in which diverse lysosomal functions are impaired, impacting multiple organs and systems. The first clinical signs and symptoms are usually unspecific and shared by hundreds of other disorders. Diagnosis of LD traditionally relies on performing specific enzymatic assays, if available, upon clinical suspicion of the disorder. However, the combination of the insidious onset of LD and the lack of awareness on these rare diseases among medical personnel results in undesirable diagnostic delays, with unchecked disease progression, appearance of complications and a worsened prognosis. We tested the usefulness of a next‐generation sequencing‐based gene panel for quick, early detection of LD among cases of idiopathic splenomegaly and/or thrombocytopenia, two of the earliest clinical signs observed in most LD. Our 73‐gene panel interrogated 28 genes for LD, 1 biomarker and 44 genes underlying non‐LD differential diagnoses. Among 38 unrelated patients, we elucidated eight cases (21%), five with LD (GM1 gangliosidosis, Sanfilippo disease A and B, Niemann‐Pick disease B, Gaucher disease) and three with non‐LD conditions. Interestingly, we identified three LD patients harboring pathogenic mutations in two LD genes each, which may result in unusual disease presentations and impact treatment. Turnaround time for panel screening and genetic validation was 1 month. Our results underline the usefulness of resequencing gene panels for quick and cost‐effective screening of LDs and disorders sharing with them early clinical signs.